Breast cancer risk and hysterectomy status: the Multiethnic Cohort Study - Woolcott, Christy G. (2008)
OBJECTIVE: The main objective was to examine the association between simple hysterectomy (without bilateral oophorectomy) and breast cancer risk. Because hysterectomy prevalence varies by ethnicity, the secondary objective was to examine whether inclusion of women with hysterectomies affects the estimates of breast cancer risk by ethnicity. METHODS: The Multiethnic Cohort Study was assembled in 1993-6 and included 68,065 women from Hawaii and Los Angeles aged 45-75 years without missing information or bilateral oophorectomy. Hysterectomy status was self-reported. After 7.7 years median follow-up, 1,862 cases of invasive breast cancer were identified. Proportional hazards models were used to estimate relative risks (RR) while controlling for known risk factors. RESULTS: Prevalence of simple hysterectomy varied from 12 to 29% among the ethnic groups (White, African American, Native Hawaiian, Japanese American, and Latina). Overall, hysterectomy was not associated with breast cancer risk (RR=0.98). Although the RRs were nonsignificantly elevated by 15% in White women and nonsignificantly reduced by 15% in Latinas of non-US origin, the variation by ethnicity was not significant (p(interaction)=0.48). The breast cancer risk associated with ethnicity was very similar when estimated with and without women with hysterectomies. CONCLUSIONS: This study suggests that simple hysterectomy status does not alter breast cancer risk. Therefore, inclusion of women with simple hysterectomies does not substantially change estimated risk of breast cancer by ethnicity.